Factors Affecting Bone Mineral Mass Loss After Lower-Limb Fractures in a Pediatric Population. Issue 4 (June 2015) - Ceroni, Dimitri; Martin, Xavier; Kherad, Omar; Salvo, Davide; Dubois-Ferrière, Victor
<x xml:space="preserve">Abstract</x> Background: The purpose of this study was to assess the effects of the durations of cast immobilization and non–weight-bearing periods, and decreases in vigorous physical activity (VPA) on bone mineral parameters in a pediatric population treated for a lower-limb fracture. Methods: Fifty children and teenagers who had undergone a cast-mediated immobilization for a leg or ankle fracture were prospectively recruited. The durations of cast immobilization and non–weight-bearing periods were recorded for each participant. Dual-energy x-ray absorptiometry scans were performed at the time of fracture treatment (baseline) and at cast removal. Physical activity during cast immobilization was assessed using accelerometers. Results: A strong negative correlation was found between the total duration of cast immobilization and decreases in both calcaneal bone mineral density (BMD) (r=−0.497) and total lower-limb bone mineral content (BMC) (r=−0.405). A strong negative correlation was also noted between the durations of the non–weight-bearing periods and alterations in calcaneal BMD (r=−0.420). No apparent correlations were found between lower BMD and BMC and decreased VPA. Conclusions: Bone mineral loss was correlated to the total duration of cast immobilization for all measurement sites on the affected leg, whereas it was only correlated to the durations of non–weight-bearing periods for calcaneal BMD and total lower-limb BMC. However, no correlations were noted between bone mineral loss and decreased VPA.